Phương pháp giá bán lẻ trong xác định giá hàng tồn kho - Nguyễn, Thị Kim Oanh (Tạp chí Kế toán và Kiểm toán, 2020)
According to Circular 200/2014QD-BTC issued by the Ministry of Finance on 22th, December 2014, retailers can adopt the Retail Inventory Method to value ending inventories. For this method, "a reasonable percentage of gross profit" is the key, but has not been guided. This creates a rooms for various interpretations. Thus, this paper aims to introduce two possible methods that might be used in valuing ending inventories based on different ways of calculating " a reasonable percentage of gross profit" namely the estimation method and the actual cost-to-ratail ratio method